2017
DOI: 10.1146/annurev-micro-090816-093325
|View full text |Cite
|
Sign up to set email alerts
|

A Symphony of Cyclases: Specificity in Diguanylate Cyclase Signaling

Abstract: Cyclic diguanylate (c-di-GMP) is a near universal signaling molecule produced by diguanylate cyclases that can direct a variety of bacterial behaviors. A major area of research over the last several years has been aimed at understanding how a cell with dozens of diguanylate cyclases can deploy a given subset of them to produce a desired phenotypic outcome without undesired cross talk between c-di-GMP-dependent systems. Several models have been put forward to address this question, including specificity of cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 69 publications
(93 reference statements)
2
83
0
4
Order By: Relevance
“…These observations confirmed that biofilm formation is not directly promoted by a higher concentration of c-di-GMP in the cell but is regulated by discrete and interconnected pathways that respond to local concentrations of c-di-GMP 26 . The DipA protein plays a crucial role in biofilm formation and dispersion in P. aeruginosa as a ∆dipA mutant exhibits reduced swarming motility, increased EPS production and reduced cell dispersal 35 .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…These observations confirmed that biofilm formation is not directly promoted by a higher concentration of c-di-GMP in the cell but is regulated by discrete and interconnected pathways that respond to local concentrations of c-di-GMP 26 . The DipA protein plays a crucial role in biofilm formation and dispersion in P. aeruginosa as a ∆dipA mutant exhibits reduced swarming motility, increased EPS production and reduced cell dispersal 35 .…”
Section: Discussionsupporting
confidence: 67%
“…Cyclic diguanylate (c-di-GMP), a near universal intracellular signaling messenger, regulates many aspects of bacterial growth and behavior 26,27 , including the transition from motile-to-sessile lifestyle leading to biofilm formation and virulence 28,29 . Intracellular levels of c-di-GMP can be modulated through the balanced activities of two classes of enzymes: (i) the diguanylate cyclases (DGCs) that synthetize c-di-GMP from two GTPs and (ii) the diguanylate phosphodiesterases (PDEs) that degrade c-di-GMP in pGpG and GMP 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated previously that the l-site of GcbC contributes to the interaction of this enzyme with LapD (13). This direct interaction model was proposed as one means to confer signaling specificity (12, 14).…”
Section: Introductionmentioning
confidence: 99%
“…cyclic-diguanylate monophosphate (c-diGMP) (21). c-diGMP is produced by DGCs, typically having a GG(D/E)EF domain and is degrade by phosphodiesterases (PDE), often having an EAL domain (22). The ZM4 genome has five genes annotated to have GG(D/E)EF and/or EAL domains ( Fig.…”
Section: Clustering Of Cells Into Flocs or Biofilms Is Commonly Coordmentioning
confidence: 99%